Peranan Penyuluh Pertanian dalam Pengembangan Kelompok Tani di Desa Lise Kecamatan Panca Lautang Kabupaten Sidrap - Rusman Rusman; Yusriadi Yusriadi; Nurhaedah Nurhaedah (Universitas Muslim Maros, 2023)
Farmers are the main actors in agricultural production activities and are part of the Indonesian people who need to improve their welfare and intelligence. With the extension, it is hoped that all agricultural information that develops can be absorbed and accepted by farmers, the more information that is used by farmers, the more effective the extension will be. This study aims to determine the level of the role of extension workers in the development of farmer groups in Lise Village, Panca Lautang District, Sidrap Regency and to find out whether there is a strong relationship between the role of agricultural extension workers in the development of farmer groups in Lise Village, Panca Lautang District, Sidrap Regency. Data collection techniques used are direct observation techniques, questionnaires and documentation. The data analysis technique used is analyzed using the Likert SkalaScale analysis technique. The results showed that the role of agricultural extension workers in the development of farmer groups in Lise Village, Panca Lautang District, Sidrap Regency was classified as high with a value of 75%. This is seen from the role of agricultural instructors in developing farmer groups as facilitators, motivators, and mediators, there is a significant relationship. This shows the high level of the role of agricultural extension workers in the development of farmer groups and there is a significant relationship between the role of agricultural extension workers in the development of farmer groups in Lise Village, Panca Lautang District, Sidrap Regency.